The Integration of Islamic Values and Bimanese Customary Law in the Judicial System of the Majelis Syara’ in the Nineteenth Century: A Study of Religiosity and Local Culture - Anggar Putra; Moh. Hidayatullah A.K Husein; Nasution; Nenden Herawaty Suleman; Abdul Fajri Kolopita (Universitas Negeri Jakarta, 2026)
The integration of Islamic law and customary norms (adat) is a defining characteristic of the Indonesian legal system, yet studies examining how this integration was institutionalized in judicial practices within Eastern Indonesia remain limited. This study aims to analyze the integration of Islamic values and Bima customary law within the Majelis Syara’ judicial system, and to explicate the role of religiosity and local culture in shaping the social legitimacy of judicial authority in the 19th-century Bima Sultanate. Employing a qualitative method with socio-legal and historicalinterpretative designs, data were gathered through the analysis of historical manuscripts, archival documents of the Bima Sultanate, and literature reviews, complemented by interviews with local historians, cultural observers, and heritageinstitution representatives. Data analysis was conducted using historical-critical interpretation and source triangulation. The findings reveal that the Majelis Syara’ functioned as a judicial institution that harmonized Shafi'i jurisprudence (fiqh) with Bima customary values, specifically Maja Labo Dahu and Sara Dana Mbojo. This integration was reflected in judicial principles, evidentiary mechanisms, dispute resolution, and the imposition of sanctions oriented toward justice and the maintenance of social harmony. The legitimacy of the 19th-century Bima judiciary was forged through the interaction between Islamic law, adat, clerical authority, and sultanate power. These findings contribute to the discourse on Islamic legal pluralism by demonstrating that legal authority in the case of Bima was constructed not merely through the enforcement of religious norms, but through a process of negotiation between religious texts, local traditions, and political structures that yields a socially accepted system of justice.